Preclinical evaluation of an 18F-labeled N ε-acryloyllysine piperazide for covalent targeting of transglutaminase 2 - Robert Wodtke; Markus Laube; Sandra Hauser; Sebastian Meister; Friedrich-Alexander Ludwig; Steffen Fischer; Klaus Kopka; Jens Pietzsch; Reik Löser (EJNMMI Radiopharmacy and Chemistry, 2024)
Abstract Background Transglutaminase 2 (TGase 2) is a multifunctional protein and has a prominent role in various (patho)physiological processes. In particular, its transamidase activity, which is rather latent under physiological conditions, gains importance in malignant cells. Thus, there is a great need of theranostic probes for targeting tumor-associated TGase 2, and targeted covalent inhibitors appear to be particularly attractive as vector molecules. Such an inhibitor, equipped with a radionuclide suitable for noninvasive imaging, would be supportive for answering the general question on the possibility for functional characterization of tumor-associated TGase 2. For this purpose, the recently developed 18F-labeled N ε-acryloyllysine piperazide [ 18 F]7b, which is a potent and selective irreversible inhibitor of TGase 2, was subject to a detailed radiopharmacological characterization herein. Results An alternative radiosynthesis of [ 18 F]7b is presented, which demands less than 300 µg of the respective trimethylammonio precursor per synthesis and provides [ 18 F]7b in good radiochemical yields (17 ± 7%) and high (radio)chemical purities (≥ 99%). Ex vivo biodistribution studies in healthy mice at 5 and 60 min p.i. revealed no permanent enrichment of 18F-activity in tissues with the exception of the bone tissue. In vivo pretreatment with ketoconazole and in vitro murine liver microsome studies complemented by mass spectrometric analysis demonstrated that bone uptake originates from metabolically released [18F]fluoride. Further metabolic transformations of [ 18 F]7b include mono-hydroxylation and glucuronidation. Based on blood sampling data and liver microsome experiments, pharmacokinetic parameters such as plasma and intrinsic clearance were derived, which substantiated the apparently rapid distribution of [ 18 F]7b in and elimination from the organisms. A TGase 2-mediated uptake of [ 18 F]7b in different tumor cell lines could not be proven. Moreover, evaluation of [ 18 F]7b in melanoma tumor xenograft models based on A375-hS100A4 (TGase 2 +) and MeWo (TGase 2 −) cells by ex vivo biodistribution and PET imaging studies were not indicative for a specific targeting. Conclusion [ 18 F]7b is a valuable radiometric tool to study TGase 2 in vitro under various conditions. However, its suitability for targeting tumor-associated TGase 2 is strongly limited due its unfavorable pharmacokinetic properties as demonstrated in rodents. Consequently, from a radiochemical perspective [ 18 F]7b requires appropriate structural modifications to overcome these limitations.